Implementasi Diplomasi Pendidikan Anak Migran Indonesia di Sekolah Indonesia Kuala Lumpur - Ami Bunga Wulandari; Risnanosanti; Eli Rustinar (CV. Multi Kreasi Media, 2022)
This study discusses Indonesia’s diplomacy through the field of education in Indonesia-Malaysia bilateral relations in the Introduction to School Field activity integrated with the International Real Work Lecture held at the Indonesian School in Kuala Lumpur from July to August 2022. The purpose of this activity is to find out how diplomacy the public through education can play an important role especially in reducing the negative perception between the two parties. Diplomacy is also a means for Indonesian students to cultivate a sense of love for their country, so that the children of migrants know and appreciate the original culture of Indonesia, as well as being able to increase the number of Indonesian students in Malaysia. On the other hand, public diplomacy in the field of education is the right step to promote Education Institutions. The method used is qualitative. Data collection techniques are done through documentation and interviews. The result found in the activity of Introduction to the Field of Education integrated with this International Real Work Lecture is that the Kuala Lumpur International School becomes a container of educational diplomacy for Indonesian migrant children in Malaysia. In the service process at the Indonesian School Kuala Lumpur, several problems were found related to the requirements to enter the school, such as the lack of documents, which resulted in some children being forced to study at Sanggar Belajar under the auspices of the Indonesian School Kuala Lumpur as a measure to equalize education as well as educational diplomacy for migrant children. Indonesia in Malaysia.